Factors affecting swallow outcome following treatment for advanced oral and oropharyngeal malignancies. Issue 1 (4th April 2013) - Kalavrezos, Nicholas; Cotrufo, Stefano; Govender, Roganie; Rogers, Pauline; Pirgousis, Phil; Balasundram, Sathesh; Lalabekyan, Bagrat; Liew, Colin
<x xml:space="preserve">Abstract</x> Background Treatment for tumors of the oral cavity and the oropharynx disrupts normal swallow function. The ability for oral diet postoperatively varies and may be influenced by surgery and patient‐related factors. Methods In all, 114 patients treated with surgery with and without chemoradiotherapy for advanced oral/oropharyngeal cancer were recruited. Clinicopathologic tumor parameters and reconstruction modalities were recorded. Swallow function was determined by oral intake, using the Functional Oral Intake Scale (FOIS) pretreatment and posttreatment. Results The median time to first attaining swallow function was 14 days. Patients were less likely to attain tube independence within 1 year of surgery if they received radiotherapy or had a low FOIS score preoperatively. Patients' time to first attaining swallow function postsurgery was inversely related to the FOIS score presurgery. Conclusions Swallow function recovery postsurgery is better in patients with higher FOIS presurgery, smaller tumors, and no requirement for radiotherapy. © 2013 Wiley Periodicals, Inc. Head Neck36: 47–54, 2014